A novel GIS-MCDA-based spatial habitat suitability model for Posidonia oceanica in the Mediterranean - Bakirman, Tolga; Gumusay, Mustafa Umit (SPRINGER, 2020)
Seagrasses are extremely productive flowering plants that produce oxygen by photosynthesis in the marine environment. They are globally in decline and can become endangered due to human activities and natural hazards. In order to maintain seagrass biodiversity, suitable habitats for this species must be determined and marine protected areas must be established. Recent technology allows acoustic systems to collect accurate high resolution data of the seafloor. Additionally, cost-effective optical satellite images, which provide wide coverage, have been used in various benthic studies. In this study, a habitat suitability model was developed using acoustic and optical data for Posidonia oceanica in Gulluk Bay, Turkey, SE Mediterranean, by applying the geographic information system-multi-criteria decision analysis and remote sensing techniques. Various criteria, namely, depth, sheltered area, slope, sediment yield, and topographic position index, were weighted using the analytic hierarchy process method. The model was able to identify suitable habitats for seagrass with 76% accuracy. The proposed model in the study allows fast, temporal, cost-effective, and sustainable production of seagrass habitat maps.
Keywords: Seagrass; Analytical hierarchy process; Remote sensing; Marine ecosystem; Mapping; MULTICRITERIA DECISION-ANALYSIS; HIERARCHY PROCESS; PREDICTIVE MODEL; RESTORATION; MANAGEMENT; SELECTION; MARINE; DEPTH; Environmental Sciences & Ecology